An Empirical Investigation of Technology Readiness Among Working Professionals in Ethiopia - Belli, Shivkumar M.; Shivaji, Waghamare (Prabandhan: Indian Journal of Management, 2015)
Technology readiness as a concept offers an impetus for researchers and practitioners to gain customers’ readiness to embrace and interact with technology in a more comprehensive manner. The Technology Readiness Index (TRI) scale has been widely used to assess technology readiness in a variety of countries and cultures. However, there are a limited number of studies which have focused on developing countries such as Ethiopia to explore the people-technology interaction. Ethiopia is one of the fastest growing economies of Africa, and hence, insights into Ethiopian consumers is important to the global marketplace. At the same time, with macroeconomic changes, Ethiopian consumers would also move from traditional to mainstream consumerism where technology is an important dimension of the marketing process. Therefore, this article focused on assessing technology readiness in general among Ethiopian working professionals using the Technology Readiness Index. The data were collected from individuals working in government and private offices based in Addis Ababa, the capital of Ethiopia, during July-September 2014. The results of the study discussed the technology readiness of working professionals and also compared results from previous studies conducted in different geographies like U.S., China, and Europe using the Technology Readiness Index scale.